2018
DOI: 10.1155/2018/3610921
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Adsorption and Desorption of Cu(II) in Silty Clay

Abstract: Heavy metals such as Cu(II) are widespread in the environment, and the impact of heavy metals on the environment of soils depends on the ability of soils to immobilize these pollutants. It is necessary to investigate the mechanism of interaction between heavy metal and soil from a soil remediation perspective. In this study, a series of experiments were conducted to investigate the adsorption and desorption behavior of Cu(II) in silty clay. Several impact factors such as pH, organic matter, temperature, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The sorption of metal complex dyes onto pine sawdust particles was also successfully interpreted by the Elovich equation ( Özacar and Şengil, 2005 ). The applicability of the Elovich model in the case of SG dye adsorption by GWTW suggests it is a heterogeneous diffusion process ( Xie et al., 2018 ).
Figure 5 Kinetic experimental data and modeling for the adsorption of SG dye by GWTW.
…”
Section: Resultsmentioning
confidence: 99%
“…The sorption of metal complex dyes onto pine sawdust particles was also successfully interpreted by the Elovich equation ( Özacar and Şengil, 2005 ). The applicability of the Elovich model in the case of SG dye adsorption by GWTW suggests it is a heterogeneous diffusion process ( Xie et al., 2018 ).
Figure 5 Kinetic experimental data and modeling for the adsorption of SG dye by GWTW.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Elovich model is more suitable for the adsorption kinetics of sediments or soils where there are large changes in activation energy (Nitish et al 2017). According to the model, the results showed that the adsorption kinetics of Cu(II) was a heterogeneous diffusion process during which the activation energy changed significantly (Gunasundari 2017;Xie et al 2018). The adsorption of Cu(II) was positively correlated with the τ, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption isotherm is used to describe the relationship between adsorption capacity and concentration of the adsorbate in solution after reaching equilibrium on the solid phase (Xie et al 2018;Yan et al 2018;Botello-Gonzalez et al 2019). Here, the Langmuir, Freundlich, Temkin and Dubinin Radushkevic models were used to evaluate the adsorption isotherm process of Cu(II) by the lake sediments under different hydrodynamic conditions.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…4, and Freundlich eq. 5) [24] were tested in the fitting of the degradation data of Sandocryl dye by Ca-ALG/Ag nanocomposite beads titanium [25] [26]. , , are the Langmuir, Freundlich, and Timken, adsorption equilibrium constants, respectively; and are the equilibrium concentration, and the adsorption capacity, respectively.…”
Section: Isothermal Studymentioning
confidence: 99%